Differential sensitivity to the acute psychotomimetic effects of delta-9-tetrahydrocannabinol associated with its differential acute effects on glial function and cortisol. Issue 11 (27th August 2022) - Colizzi, Marco; Weltens, Nathalie; Lythgoe, David J; Williams, Steve CR; Van Oudenhove, Lukas; Bhattacharyya, Sagnik
Abstract: Background: Cannabis use has been associated with psychosis through exposure to delta-9-tetrahydrocannabinol (Δ9-THC), its key psychoactive ingredient. Although preclinical and human evidence suggests that Δ9-THC acutely modulates glial function and hypothalamic-pituitary-adrenal (HPA) axis activity, whether differential sensitivity to the acute psychotomimetic effects of Δ9-THC is associated with differential effects of Δ9-THC on glial function and HPA-axis response has never been tested. Methods: A double-blind, randomized, placebo-controlled, crossover study investigated whether sensitivity to the psychotomimetic effects of Δ9-THC moderates the acute effects of a single Δ9-THC dose (1.19 mg/2 ml) on myo-inositol levels, a surrogate marker of glia, in the Anterior Cingulate Cortex (ACC), and circadian cortisol levels, the key neuroendocrine marker of the HPA-axis, in a set of 16 healthy participants (seven males) with modest previous cannabis exposure. Results: The Δ9-THC-induced change in ACC myo-inositol levels differed significantly between those sensitive to (Δ9-THC minus placebo; M = −0.251, s.d. = 1.242) and those not sensitive ( M = 1.615, s.d. = 1.753) to the psychotomimetic effects of the drug ( t (14) = 2.459, p = 0.028). Further, the Δ9-THC-induced change in cortisol levels over the study period (baseline minus 2.5 h post-drug injection) differed significantly between those sensitive to (Δ9-THC minus placebo; M = −275.4, s.d. = 207.519) and those not sensitive ( M = 74.2, s.d. = 209.281) to the psychotomimetic effects of the drug ( t (13) = 3.068, p = 0.009). Specifically, Δ9-THC exposure lowered ACC myo-inositol levels and disrupted the physiological diurnal cortisol decrease only in those subjects developing transient psychosis-like symptoms. Conclusions: The interindividual differences in transient psychosis-like effects of Δ9-THC are the result of its differential impact on glial function and stress response.